Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1088/0031-9155/37/10/010
|View full text |Cite
|
Sign up to set email alerts
|

Tissue maximum ratios (and other parameters) of small circular 4,6,10,15 and 24 MV X-ray beams for radiosurgery

Abstract: Small, circular, x-ray beams are commonly used for radiosurgery applications. Dosimetric characteristics of 4, 6, 10, 15 and 24 MV circular x-ray beams ranging in size from 10 to 40 mm are reported. These characteristics include the measurement of TMR, beam profiles and relative output factors. Measurements of these parameters were performed in a solid water phantom using film, a small diode, small parallel-plate and cylindrical ionization chambers and TLD. Comparison of relative dose measurements of small, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
9

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 10 publications
5
55
0
9
Order By: Relevance
“…7,8 With ion chambers, spatial resolution is limited by physical size of ionization cavity. [9][10][11][12][13] Diodes, on the other hand, suffer limitation from energy dependence, [14][15][16] especially for photon beams. For proton beams, point-by-point ion-chamber measurements are desired to accurately ( 1 mm) determine position of the Bragg-peak and corresponding distal edge.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 With ion chambers, spatial resolution is limited by physical size of ionization cavity. [9][10][11][12][13] Diodes, on the other hand, suffer limitation from energy dependence, [14][15][16] especially for photon beams. For proton beams, point-by-point ion-chamber measurements are desired to accurately ( 1 mm) determine position of the Bragg-peak and corresponding distal edge.…”
Section: Introductionmentioning
confidence: 99%
“…In general, we observed a shift to greater depth of d max with increasing fi eld sizes, with slightly same depth of d max for fi eld size of 12.5 mm to 22.5 mm and generally increased starting at fi eld size of 25 mm to 45 mm. Serago et al (1992) & Verhaegen et al (1998 also reported that similar shift of d max to greater depth with increasing fi eld size for a 6 MV accelerator. Such observation is opposite to traditional radiation therapy fi elds where d max decreases as fi eld size increases.…”
Section: Dose Verificationmentioning
confidence: 72%
“…Die Ionisationskammer stört einerseits die Ausbildung des zu messenden Teilchenflusses und integriert andererseits räum-lich über unterschiedliche Sekundärelektronendichten. Die Gleichheit der beiden Tiefendosiskurven, die mit dem Silizium-und dem Diamantdetektor aufgenommen wurden, ist wegen der vergleichsweise [12] sehr geringen Größe des in dieser Arbeit beschriebenen Siliziumdetektors zu erwarten.…”
Section: Materials Und Methoden Bestrahlungsgeräteunclassified
“…Damit diese zusätzlich im Strahlengang angeordneten Kollimatoren genutzt werden können, müssen ihre dosimetrischen Eigenschaften bekannt sein und im Bestrahlungsplanungsprogramm implementiert werden. Für die nötigen dosimetrischen Messungen der Grunddaten (Querprofile, Tiefendosiskurven, Outputfaktoren) können herkömmliche Messmittel wie Ionisationskammern nur begrenzt [12] und Filme nur mit hohem Aufwand genutzt werden [3]. Ziel der dosimetrischen Messung der Bestrahlungsplanungsgrunddaten sollte es aber sein, mit nur einem Messmittel einen lückenlosen Datensatz hoher Qualität für alle verfügbaren Kollimatoren zu erstellen.…”
Section: Introductionunclassified
See 1 more Smart Citation